Análisis de la reactivación económica del sector automotriz y su incidencia en los ingresos fiscales en el periodo 2020-2024 - Zambrano Vega, Lisbeth Gabriela (2025)
The automotive sector encompasses subsectors such as production (domestic assembly) and imports, vehicles, and auto parts. The COVID-19 pandemic impacted economies worldwide, creating new production and commercial scenarios. Economic recovery required the commitment of both the public and private sectors. Ecuador, an economy whose macroeconomic figures already presented some warning signs prior to the pandemic, reinforced previous measures and implemented others that, along with initiatives from vehicle dealerships, finance companies, and aftermarket repair shops, drove a recovery in the sector in 2021 and 2022. Public policies include tariff incentives for new technologies such as electricity; parameters for the scrapping and replacement of vehicles; financial relief, among others. In the second half of 2020, the private sector took on new challenges in environments unfamiliar to some segments of the population. This paved the way for the first virtual fair. New forms of direct financing from dealerships and initiatives such as buying clubs emerged......